Quality evaluation of ginger tea (Instant salabat) - Alcaraz, Jeanly Modesto (Miagao, Iloilo, Philippines University of the Philippines School of Science and Technology, 2006)
The quality of giner tea or instants salabat was evaluated through its physico-chemical and microbiological characteristics.
Sotech thesis.
Keywords: Ginger tea